Public sector wage premium and output volatility in the European Union - Vilerts, Karlis (Business, Management and Economics Engineering, 2018)
This study seeks to uncover the role played by the public sector wage premium in explaining the output volatility. Furthermore, the study also explores the factors that might substantiate the cross-country differences in the volatility of the public sector wage premium. Using cross-sectional regression analysis for the European Union countries, the findings indicate that more volatile public sector wage premium is associated with higher fluctuations in the private sector employment and less stable growth. Findings also suggest that volatility of the public sector wage premium tends to be larger in countries with smaller governments and in countries where collective bargaining is the predominant regime for public sector wage setting.